The Term Structure of Currency Futures' Risk Premia - Kerstin Bernoth; Jürgen von Hagen; Caspar de Vries (Journal of Money, Credit and Banking, 2022)
The use of futures instead of forwards exchange contracts completes the ma-turity spectrum of the correlation between spot yields and the premium. Wefind that the forward premium puzzle appears to be a precrisis phenomenonand is only observed for maturities longer than about 1 month. Differencesin the exposure to risk help to explain cross-sectional spreads in currency ex-cess returns. However, this only applies for medium and longer maturities.Considering that most studies that test the validity of a risk-based approachto currency excess returns focus on short maturity securities, this explainswhy this approach is so often rejected.
Additional information: Open access funding enabled and organized by Projekt DEAL
Keywords: F31; F37; G12; G13; G15; 330; forward premium puzzle; uncovered interest parity; futures rates; price of risk; currency excess returns; capital asset pricing mode